Parents’ Involvement in Students’ Academic Achievement in Distance Learning Process During the Pandemic of Covid-19 - Yohana Eva Mau Kasi; Suparno Suparno; Abdul Asib (RIRAI Publisher, 2021)
This study examined the parents’ involvement in students’ Distance Learning during the pandemic of Covid-19 concerning with the school’s policy. This research aimed to explore the private junior high school students’ academic achievement in the pandemic of Covid-19 which was influenced by social factors, such as teachers, parents’ motivational beliefs (Hoover-Dempsey & Sandler, 1995) and home-based and school-based parental involvement (Epstein, 1995). Qualitative method was used to do this study specifically employed a case study design. Questionnaire and semi-structured interview were used to collect the data. 20 parents, eight grade students, homeroom teacher and principle would be the participants in this study. Likert scale and open-ended questionnaire were used to know the participants’ responses on parent’s involvement in children’s education in the Distance Learning. Semi-structured interview would be used to interview the three parents, three students, homeroom teacher and principle for exploring their deep opinions on parental involvement in children’s education success in Distance Learning during the pandemic of Covid-19. The results showed the positives beliefs of parents, students, and school in parents’ involvement in order to influence students’ academic achievement, especially in Distance Learning. At home, parents agreed to control and guide their children in doing the assignments, while at school, they took part in school’s meetings and seminars held by the school.